2009
DOI: 10.1039/b900977a
|View full text |Cite
|
Sign up to set email alerts
|

A thermally cured 9,9-diarylfluorene-based triaryldiamine polymer displaying high hole mobility and remarkable ambient stability

Abstract: We have synthesized and characterized a novel thermally polymerizable triaryldiamine monomer (VB-FNPD) possessing a styrene-functionalized 9,9-diarylfluorene core and have used time-of-flight transient photocurrent techniques to investigate the hole transport properties of its solution-processed and subsequently thermally cured (170 C) polymer films. This novel polymeric material exhibits nondispersive hole transport behavior with a high hole drift mobility (up to 10 À4 cm 2 V À1 s À1 ). The film displayed rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…It has been reported that HAT-CN has a more stable interface 23 24 and only dissolves in acetone 25 ; therefore, HAT-CN is the better HIL here to withstand immersion in DI water. In addition, the cross-linkable derivative of NPD, VB-FNPD, is used here as HTL which displays remarkable ambient stability 26 27 . Moreover, the alignment of electronic energy levels at HAT-CN/VB-FNPD reveals that the interface between HAT-CN and VB-FNPD layers can be assumed as ohmic contact, which improves hole injection 25 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HAT-CN has a more stable interface 23 24 and only dissolves in acetone 25 ; therefore, HAT-CN is the better HIL here to withstand immersion in DI water. In addition, the cross-linkable derivative of NPD, VB-FNPD, is used here as HTL which displays remarkable ambient stability 26 27 . Moreover, the alignment of electronic energy levels at HAT-CN/VB-FNPD reveals that the interface between HAT-CN and VB-FNPD layers can be assumed as ohmic contact, which improves hole injection 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The PEDOT:PSS films were then dried in air at 135 °C for 30 min. Solution of VB‐FNPD (10 mg·mL −1 ) was prepared using chlorobenzene as solvent, and the VB‐FNPD films were then spin‐coated onto the PEDOT:PSS/ITO substrates 25. The samples were then baked on a hot plate at 100 °C for 30 min to remove the solvent and then 230 °C for 90 min for crosslinking.…”
Section: Methodsmentioning
confidence: 99%
“…There are a few materials reported so far for perovskite LEDs that meet these requirements. [ 40–43 ] In this study, we used the new cross‐linkable HTL of VB‐FNPD, which has transparency, the proper HOMO and LUMO levels of 5.4 and 2.4 eV, relatively high hole‐carrier mobility of 1.00 × 10 −4 cm 2 V −1 s −1[ 44 ] compared to commercial HTL of polyvinylcarbazole (PVK, hole mobility: 2.50 × 10–6 cm 2 V −1 s −1[ 45 ] ), cross‐linking properties for multilayer preparation, and the proper surface energy based on the contact angle data. First, for the hole‐injection property of VB‐FNPD, the hole‐only device (HOD) including PVK or VB‐FNPD was fabricated in all three colors.…”
Section: New Hole‐transporting Materials For Peqd Devicementioning
confidence: 99%